2007
DOI: 10.3844/jssp.2007.117.122
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Use Their Cars: A Case Study In Malaysia

Abstract: Abstract:In Malaysia, the rapid increase in the use of own transport prompted by inadequate public transport has resulted in increased traffic congestion, accidents, inadequate parking space and air pollution among other evils. This study sought to identify the factors preventing own transport users from shifting to public transport and to develop model shift from car to public transport in order to formulate the policies to achieve this. A survey was carried out on users of private and public (both bus and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Private vehicle usage has increased over the last few decades in most of the urban areas especially in developed and developing countries attributed possibly to the poor management of PT services (Kamba et al, 2007;Kasipillai and Chan, 2008;Nurdden et al, 2007;Steg, 2003). PT is often perceived to be poor alternative compared to private vehicles (Steg, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Private vehicle usage has increased over the last few decades in most of the urban areas especially in developed and developing countries attributed possibly to the poor management of PT services (Kamba et al, 2007;Kasipillai and Chan, 2008;Nurdden et al, 2007;Steg, 2003). PT is often perceived to be poor alternative compared to private vehicles (Steg, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of PBT services, research done by Andaleeb et al (2007) argued that the main factors to increase the satisfaction level of the regular bus users are the comfort level of the bus, the staff behavior, the number of bus transit point to reach the destination, supervision and waiting facilities provided. In Malaysia, a few researches have been conducted to examine different characteristics of Malaysian citizens who are favoring private transportation as well as factors influencing the individual selection of the mode of transportation (Kamba et al, 2007;Kasipillai and Chan, 2008;Mohamad and Kiggundu, 2007;Sheikh et al, 2006). Some studies showed that an efficient PT system with reduced bus travel time and cost is essential to encourage especially motorists or car drivers to utilize the PBT services (Nurdden et al, 2007;Sheikh et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out by Mohamad and Kiggundu [26], Abdul Kadir et al [27], Kamba et al [28] in Klang Valley, Rastogi [5] and Tiwari [9] investigated factors affecting mode choice preferences. Geographical and cultural variations in factors affecting travel mode choice are studied by Desai and Joshi [13].…”
Section: Selection Of Variables Based On Variable Ranking Resultsmentioning
confidence: 99%
“…In addition, according to Ohmae (1995), countries with US$3,000 gross national product (GNP; considered income threshold) has a strong and steady demand for consumer goods, such as relatively cheap motorcars, while a GNP of US$5,000 would demand high quality and posh cars. Therefore, the increase in new vehicle registration that grows in tandem with economic growth (Ohmae, 1995) has caused problems, such as worsening traffic congestion, road accidents, air and noise pollution in Malaysia (Mohamad and Kiggundu, 2007;Kamba et al, 2007). Figure 1 shows vehicle ownership growing yearly except in 1998 (a consequence of the 1997 Asian financial crisis) and 2009 (due to 2008 global financial crisis).…”
Section: Public Bus Transport and Private Vehicles In Malaysiamentioning
confidence: 99%